PERFORMANCE OF MAIZE-CHICKPEA SEQUENCE AT DIFFERENT SOWING DATES AND NITROGEN MANAGEMENT PRACTICES - M. RATNAM (The Journal of Research ANGRAU, 2018)
Studies were conducted on clay soils for two years to find out the influence of sowing time and nitrogen levels on the yield performance and yield attributing characters in maize-chickpea sequence. Sowing dates followed and nitrogen levels applied to maize and chickpea significantly influenced the yield attributes, yield and monetary returns of both the crops during both the years of the experiment. Highest grain and straw yield, higher amount of N uptake by kernel and stover and higher B:C Ratio were recorded by both the crops when maize was sown on the 1st FN of July with 200% RDN and 100% RDN applied to succeeding chickpea during Kharif and Rabi of 2013-14 and 2014-15.